Analysis of Financial Ratios on The Performance of Muamalat Indonesia Bank - Wita Sri Nurlatipah; Fadali Rahman; Mohamad Toha (Majapahit Journal of Islamic Finance and Management, 2022)
This study aims to determine the effect of financial ratios (NPL, CAR, LDR, BOPO) simultaneously on the performance of Muamalat Indonesia Bank from 2008-2018. In this study, the researchers used a type of quantitative research with a descriptive and verification research approach because of the variables to be examined for their relationship and the purpose of presenting a structured picture. This research is a quantitative study with time series data. The type of data used in this study is secondary data in the form of data for all variables, namely Return on Assets (ROA), Non-Performing Loans (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Operating Cost Income Operational (BOPO). This secondary data was obtained by the method of observing financial ratios registered during the observation from 2008 to 2018. Corporate financial data for that period is available at www.idx.co.id. Data collection techniques used are observation and recording and linear regression models are used to determine whether there is a significant influence of one variable with another variable. For testing the hypothesis, it used the t-test and F-test.